Loss of Caᵥ1.3 RNA editing enhances mouse hippocampal plasticity, learning, and memory - Zhai, Jing (2023)
L-type CaV1.3 calcium channels are expressed on the dendrites and soma of neurons, and there is a paucity of information about its role in hippocampal plasticity. Here, by genetic targeting to ablate CaV1.3 RNA editing, we demonstrate that unedited CaV1.3ΔECS mice exhibited improved learning and enhanced long-term memory, supporting a functional role of RNA editing in behavior. Significantly, the editing paradox that functional recoding of CaV1.3 RNA editing sites slows Ca2+-dependent inactivation to increase Ca2+ influx but reduces channel open probability to decrease Ca2+ influx was resolved. Mechanistically, using hippocampal slice recordings, we provide evidence that unedited CaV1.3 channels permitted larger Ca2+ influx into the hippocampal pyramidal neurons to bolster neuronal excitability, synaptic transmission, late long-term potentiation, and increased dendritic arborization. Of note, RNA editing of the CaV1.3 IQ-domain was found to be evolutionarily conserved in mammals, which lends support to the importance of the functional recoding of the CaV1.3 channel in brain function.